Pengaruh ITO dan WCTO terhadap NPM pada Perusahaan Farmasi - Sekar Wulan Wiwitanti; Rosma Pakpahan; Endang Hatma Juniwati (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This research aims to description whether there is an influence between Inventory Turnover, Working Capital Turnover to Net Profit Margin (NPM). This research uses quantitative method, so the sample that used in this research is sub-sector’s company of pharmacy that has been listed on the Indonesia Stock Exchange (IDX) for 2014-2018 period . This research used secondary data. Data analysis method used descriptive analysis and statistics analysis with using IBM SPSS 26 software. The results showed that partially, Inventory Turnover has significant effect on Net Profit Margin with positive coefficient and Working Capital Turnover has significant effect on Net Profit Margin with negative coefficient. While, simultaneous Inventory Turnover and Working Capital Turnover has significant on Net Profit Margin with R Square value is 64% and 36% residual was influenced bye other factor outside variabels researched.